Computed tomography-measured body composition can predict long-term outcomes for stage I-III colorectal cancer patients - Zhou, Han; Tian, Lei; Wu, Yiting; Liu, Sibin (Frontiers in Oncology, 2024)
Background: There remains a pressing need to identify biomarkers capable of reliably predicting prognostic outcomes for colorectal cancer (CRC) patients. As several body composition parameters have recently been reported to exhibit varying levels of prognostic significance in particular cancers, the present study was devised to assess the ability of body composition to predict long-term outcomes for CRC patients with different stages of disease.In total, this retrospective analysis enrolled 327 stage I-III CRC patients whose medical records were accessed for baseline demographic and clinical data. Primary outcomes for these patients included disease-free and overall survival (DFS and OS). The prognostic performance of different musculature, visceral, and subcutaneous fat measurements from preoperative computed tomography (CT) scans was assessed.Results: Over the course of follow-up, 93 of the enrolled patients experienced recurrent disease and 39 died. Through multivariate Cox regression analyses, the visceral/subcutaneous fat area (V/S) ratio was found to be independently associated with patient DFS (HR=1.93, 95% CI: 1.24-3.01, P=0.004), and the skeletal muscle index (SMI) as an independent predictor for OS (HR=0.43, 95% CI: 0.21-0.89, P=0.023). Through subgroup analyses, higher V/S ratios were found to be correlated with reduced DFS among patients with stage T3/4 (P=0.011), lymph node metastasis-positive (P=0.002), and TNM stage III (P=0.002) disease, whereas a higher SMI was associated with better OS in all T stages (P=0.034, P=0.015), lymph node metastasis-positive cases (P=0.020), and in patients with TNM stage III disease (P=0.020).Both the V/S ratio and SMI offer potential utility as clinical biomarkers associated with long-term CRC patient prognosis. A higher V/S ratio and a lower SMI are closely related to poorer outcomes in patients with more advanced disease.